SOCIAL STRATIFICATION IN GUNTURU VILLAGE, HERLANG DISTRICT, BULUKUMBA REGENCY - Tauzi, Azlan; Falihin, Dalilul (UNM Geographic Journal, 2022)
This study aims to: 1) Find out the description of social stratification in Gunturu Village, Herlang District, Bulukumba Regency. 2) Knowing the form of social interaction between the karaeng group and the ata group in Gunturu Village, Herlang District, Bulukumba Regency. The type of research used by the researcher is descriptive qualitative. The data collection techniques through, documentation, observation, and interviews. The data collection process carried out by the researchers included: data collection, data reduction, data presentation and conclusion drawing. The results showed 1) The description of social stratification in Gunturu Village, Herlang District, Bulukumba Regency had several indicators, namely wealth, power, honor, and knowledge. . Wealth is categorized as "appropriate", because according to the results of interviews that society really views a person's economic level, as for that it still exists today. Power here is categorized as "appropriate" because people really see a person's power and see the origin of descendants. Honor is categorized as "appropriate" because society also really views someone according to their descent. Science is categorized as "appropriate" because a person's level of knowledge and degree can make a person's strata different according to the views of society again. 2) the form of social interaction between the people of the Karaeng group and the ata group consists of cooperation, competition and dispute, cooperation is categorized as "appropriate" because the community is still working well together and helping each other is still well established, competition is categorized as "appropriate" because the community in this case there is no competition, the community lives in peace, and the dispute is categorized as "inappropriate" because the community in this case there is no competition, while the community is aware of their respective positions, as for the conflicts that exist only in conflicts with oneself that are not cause division.